Does the knowledge of the human immunodeficiency virus serostatus influence the clinical diagnostic proficiency of Kaposi's sarcoma? - L.J. van Bogaert (South African Family Practice)
Objectives: Kaposi's sarcoma is an acquired immunodeficiency syndrome (AIDS)-defining illness. A spectrum of non- Kaposi's sarcoma clinical and histopathological mimickers contributes to the potential over- or underdiagnosis of Kaposi's sarcoma. The aim of this audit was to investigate the clinical diagnostic accuracy of Kaposi's sarcoma and to find out whether or not knowledge of the human immunodeficiency virus (HIV) serostatus influenced the clinical diagnostic accuracy.